Playground [videorecording (DVD)] - Vanderbeque, Maya; Duret, Gunter; Voss, Lena Girard; Caudry, Simon (Film Movement series., 2022)
In this debut feature, the everyday reality of grade school is seen from a child's-eye-view as an obstacle course of degradation and abuse. Following seven-year-old Nora and her big brother Abel, we see Nora struggling to fit in before finding her place in the schoolyard. One day, she notices Abel being bullied by other kids, and though she rushes to protect him by warning their father, Abel forces her to remain silent, while he endures more humiliation and harassment by his peers. Transposing the gritty realism of such filmmakers like Jacques Audiard and the Dardennes Brothers to the inner world of kids, Wandel crafts an empathetic and visceral portrait of the cruelty of children, and the failure of adults to protect them.